IPTEK BAGI PRODUK EKSPOR KERAJINAN SONGKET MOTIF BALI DI KABUPATEN KARANGASEM BALI TAHUN KETIGA - Luh Made Yulyantari; IGKG Puritan Wijaya Adh (Ngayah: Majalah Aplikasi IPTEKS, 2019)
The increasing demand for songket woven fabric has led to micro businesses in the manufacture of songket weaving in the village of Sidemen which has its own characteristics from Balinese songket weaving. Songket Ayu Sidemen and UK Suastini Songket are yarn-based songket weaving businesses. The problems that occur at this time are such as the lack of a representative work place, the lack of looms that have functioned poorly due to the age of looms, processing and management of raw materials and products that have not been well managed, human resource management and management finance that needs to be improved, product packaging that is still very simple, songket weaving motifs that are still less varied, and marketing techniques that are still traditional and untouched by technology as a marketing aid. Based on the problems faced, there will be a phased activity for three years starting from the management of woven materials to product packaging and product marketing through the internet. In the first year (2016) achieving output in the form of 100% workplace improvement to be better, SME assets increased by 50%, workers could better manage woven materials and increase product quality by 20%. In the second year (2017) is the first ability of all (100%) UKM workers in making good motives and designs and able to design product packaging. Both UKM owners can do well in operational management, labor and management of woven materials, so that it can make 40% efficient use of resources. All three UKM are able to increase marketing network expansion by 50% using the latest communication technology and social media utilization. Output focus in the third year (2018) is the first application of inventory systems, financial systems and marketing systems and websites as marketing tools have been able to be applied to SME partners by 100%. Both partner UKM are able to market products to international standards for fabric products. Third, the achievement of marketing network expansion by 50% and product sales by 40%..